1992
DOI: 10.1093/ajcn/56.5.874
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake, energy expenditure, and body composition of poor rural Philippine women throughout the first 6 mo of lactation

Abstract: Between 6 and 30 wk postpartum, body weight and body-fat mass of 40 healthy, rural, lactating Filipino women decreased by 1.5 (P < 0.05) and 0.7 kg (P < 0.05), respectively. Energy intake decreased slightly (NS) from 8.84 +/- 2.05 MJ/d (2113 +/- 489 kcal/d; mean +/- SD) at 6 wk to 8.67 +/- 2.37 MJ/d (2073 +/- 566 kcal/d) at 30 wk. Basal metabolic rate (BMR) remained unchanged throughout lactation, and physical-activity level increased significantly (P < 0.05) from 1.61 +/- 0.17 x BMR at 6 wk to 1.97 +/- 0.18 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
4
32
1
Order By: Relevance
“…Alternatively, the differences observed were small enough that sample sizes of n ¼ 229 for both LACT and NPNL women would be required to show a significance at 80% power. This finding of a non-significant tendency for BMR to be higher in lactating women is in agreement with the majority of studies in both developing (Schutz et al, 1980;Singh et al, 1989;Guillermo-Tuazon et al, 1992;Madhavapeddi & Rao, 1992), and developed countries (Goldberg et al, 1991;Illingworth et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alternatively, the differences observed were small enough that sample sizes of n ¼ 229 for both LACT and NPNL women would be required to show a significance at 80% power. This finding of a non-significant tendency for BMR to be higher in lactating women is in agreement with the majority of studies in both developing (Schutz et al, 1980;Singh et al, 1989;Guillermo-Tuazon et al, 1992;Madhavapeddi & Rao, 1992), and developed countries (Goldberg et al, 1991;Illingworth et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…For example, lactating women in India, 1 -6 months pp (Madhavapeddi & Rao, 1992;Piers et al, 1995), and in Bangladesh, 2 -8 months pp (Rashid & Ulijaszek 1999), as well as food supplemented women in the Gambia, 3 -9 months pp (Lawrence et al, 1986) were essentially weight stable showing changes in body weight of less than 0.7 kg. In contrast, studies of lactating women in the Philippines, 1-8 months pp (Guillermo-Tuazon et al, 1992), as well as those in Europe (Forsum, et al, 1992;Sadurkis et al, 1988;van Raaij et al, 1991) reported weight losses of 1.3 -1.4 kg in lactating women 1 -7 months pp. In the latter, the possibility that some of the weight loss was due to dieting cannot be discounted.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, attention has focussed on lactating women and a number of studies have investigated their energy expenditure and body composition (Goldberg et al, 1991;Adair & Popkin, 1992;Forsum et al, 1992;Guillermo-Tuazon et al, 1992;Piers et al, 1995;Dewey, 1998;Butte et al, 1997Butte et al, ,1999Krebs et al, 1997;Motil et al, 1998;Spurr et al, 1998). However there have been few longitudinal studies beyond 6 months post-partum (cf Lawrence et al, 1986) and most of the subjects were well-nourished mothers (van Raaij et al, 1990;Adair & Popkin, 1992;Motil et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss of about 500 gamonth is usual during lactation and fat mass loss has been observed during lactation among tropical populations (Adair & Popkin, 1992;Guillermo-Tuazon et al, 1992) and among women from developed countries with maternal caloric restriction (Dewey, 1998). Furthermore, observed fat-mass losses during lactation are often substantially smaller than the supposed fat mobilization used in the calculations of recommendations (Butte et al, 1984;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation